2018
DOI: 10.2147/idr.s157522
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of <em>Staphylococcus aureus </em>and methicillin-resistant <em>Staphylococcus aureus </em>carriage in neonates: the role of maternal carriage and phenotypic and molecular characteristics

Abstract: BackgroundStaphylococcus aureus, particularly methicillin-resistant S. aureus (MRSA), in mothers can cause serious outcomes in neonates. We aimed to elucidate the associations of S. aureus and MRSA carriage between mothers and neonates.MethodsA prospective cohort study was conducted between August and November 2015 in two hospitals in Shenzhen, China. Chinese pregnant women and their neonates who met the inclusion criteria were included in this study; samples and relevant information were collected. We assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
20
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 43 publications
9
20
3
Order By: Relevance
“…The proportions of antibiotic resistance were higher in MRSA isolates than MSSA isolates, which is also observed in other studies [8,17]. Teicoplanin has been widely used as an anti-MRSA agent in infectious patients in the past decades [18,19], which can partially explain the high The results of CCs and STs for S. aureus isolates could demonstrate the multiple transmissions among human beings, livestock and environment, which are similar to previous studies [6,23]. We found high proportions of ST5 and ST59 in this study and these STs were also globally reported in communities [26].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The proportions of antibiotic resistance were higher in MRSA isolates than MSSA isolates, which is also observed in other studies [8,17]. Teicoplanin has been widely used as an anti-MRSA agent in infectious patients in the past decades [18,19], which can partially explain the high The results of CCs and STs for S. aureus isolates could demonstrate the multiple transmissions among human beings, livestock and environment, which are similar to previous studies [6,23]. We found high proportions of ST5 and ST59 in this study and these STs were also globally reported in communities [26].…”
Section: Discussionsupporting
confidence: 87%
“…. The proportions of virulence genes for MRSA isolates were higher than the observed studies[6,[23][24][25]. The results implied that drug users with MRSA carriage harbouring virulence associated genes, might have higher risks for relevant disease and should draw more attention.…”
mentioning
confidence: 70%
“…A meta-analysis of risk factors for MRSA colonization in the NICU showed no relationship between colonization and sex,[3] while another study reported male neonates were at increased risk of both MRSA and MSSA colonization. [22] However, our admission patterns did not elucidate an explanation for this finding nor were female neonates older than male neonates on admission. We found vaginal delivery to be a risk factor for MSSA, but not for MRSA colonization.…”
Section: Discussionmentioning
confidence: 74%
“…In Shenzhen China, 7.3% vs. 1.7% of pre-partum women were colonized with MSSA and MRSA, respectively, and vaginal delivery was associated with neonatal MSSA, but not with MRSA colonization. [22] Similarly, Top et al reported MSSA and MRSA anovaginal colonization rates of 11.8% and 0.6%, respectively, in pre-partum women, although neonatal colonization was not assessed. [23] These findings suggest that vertical transmission of S. aureus occurs, but is more relevant for MSSA than MRSA, presumably because fewer women are colonized with MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23]. The proportions of virulence genes for MRSA isolates were higher than the observed studies [6,[24][25][26]. The results implied that drug users with MRSA carriage harboring virulence associated genes, might have higher risks for relevant disease and should draw more attention.…”
Section: Discussionmentioning
confidence: 88%